Empowering Community Health Volunteers as a Strategy to Prevent Anemia in Pregnant Women: A Quasi-Experimental Study - Sentuf, Diana Rosalina; Jumrah; Idrus, Hasta Handayani; Stang; Darmawansyah (National Journal of Community Medicine, 2025)
Background: Pregnancy anemia is a significant public health issue causing postpartum hemorrhage, premature birth, and low birth weight. Empowering community health volunteers could improve compliance and improve hemoglobin levels. Methodology: The study investigates the impact of community health volunteer’s empowerment on adherence to iron supplement tablets tablet consumption and hemoglobin levels. the sample size is 62 third-trimester pregnant women (31 per group) for precision standard care using only the Maternal and Child Health book without cadre assistance. The Morisky Medication Adherence Scale-8 questionnaire was used to assess compliance. Data analysis included Chi-square and Paired Sample T test. Results: Adherence to blood tablet consumption increased significantly in the intervention group compared to the control group with a significant value of p <0.001. Hemoglobin levels also increased significantly (p-value = 0.001), and adherence to the consumption of iron supplement tablets influenced hemoglobin levels (p-value = 0.003). Conclusion: Empowering cadres in primary health facilities is effective in increasing compliance with iron supplement tablets tablet consumption, which impacts hemoglobin levels in third-trimester pregnant women.